Real time endobronchial ultrasound guided transbronchial needle aspiration of intrathoracic lymphadenopathy: an initial experience - Dar, Khurshid Ahmad; Sultan, Sheikh Tariq; Singh, Randeep; Mehfooz, Nazia; Shah, Naveed Nazir; Farooq, Syed Suraiya; Datta, Bikram Singh; Malik, Abdul Hamid; Sheikh, Bilal Ahmad; Bhat, Khalid Feroz (International Journal of Research in Medical Sciences, 2019)
Background: Conventional TBNA has been used in the evaluation of intrathoracic lymphadenopathy with varied success rates depending upon size, site and aetiology of the node. Although mediastinoscopy has higher successes but it comes at the cost of general anaesthesia, more complications and limited access to the inferior and posterior mediastinum. Endobronchial ultrasound guided transbronchial needle aspiration has the advantage of real time nodal sampling with good success rates and minimal complications. The aim of our study was to assess the diagnostic yield and safety of EBUS TBNA in the evaluation of intrathoracic lymphadenopathy. Methods: This prospective observational study was conducted at government chest diseases hospital Srinagar over a period of two years from January 2016-December 2018 on 100 consecutive patients who underwent EBUS TBNA procedure for evaluation mediastinal and hilar lymphadenopathy. The data was collected and analysed for diagnostic yield and safety profile. Results: Out of the 100 subjects included in the study 52% were males and 48% were females. Mean age of the study population was 48.5±16.65 years. Most of the nodes sampled were subcarinal in location followed by paratracheal and hilar group. Granulomatous pathology (tuberculosis and sarcoidosis) was present in 41 patients followed by malignancy in 39 patients. Anthracosis was the cause of lymphadenopathy in 4 of the patients. There were no major complications in our study. Conclusions: EBUS TBNA is an effective and safe procedure for evaluation of mediastinal and hilar lymphadenopathy.